Dispersing silicon nanoparticles in a stirred media mill - investigating the evolution of morphology, structure and oxide formation - Frank, Gerhard; Peukert, Wolfgang; Reindl, Armin; Altin, Ergün; Aldabergenova, Saule (physica status solidi (a), 2007)
Silicon nanoparticles were dispersed for 24 hours in 1-butanol using a stirred media mill. Via this process intrinsically stable suspensions (in regard to aggregation) of Si nanoparticles were produced after 6 hours of dispersing. The evolution of morphology, particle size and structure was investigated by dynamic light scattering, X-ray diffraction, Raman spectroscopy and high resolution transmission electron microscopy as a function of dispersing time. The average crystallite size decreased from about 18 nm down to about 10 nm within 24 hours of milling as determined by X-ray diffraction and Raman scattering measurements. In addition careful analysis of the Raman spectra revealed a decrease of the crystalline volume fraction from 75% down to 24% and a corresponding increase of the amorphous phase. The microstructural development with varying crystallite size and crystalline volume fraction was directly confirmed by transmission electron microscopy measurements. Elemental analysis showed an increase of oxygen content that was directly proportional to the increase in specific surface area of the silicon nanoparticles during the dispersing process. The surface chemistry of the Si nanoparticles was analyzed by diffuse reflectance infrared Fourier transform spectroscopy that indicated vibrational bands of HSi-Si 3-xO x, SiO x, and residual 1-butanol. The final product of the dispersing process seems to be a two-phase mixture of amorphous Si and Si nanocrystallites covered with SiO x on the surface. © 2007 WILEY-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.disper
Keywords: nano; particle; dispersion